From Born-Physical to Born-Virtual: Augmenting Intelligence in Digital Libraries 24th International Conference on Asian Digital Libraries, ICADL 2022, Hanoi, Vietnam, November 30 - December 2, 2022, Proceedings - Tseng, Yuen-Hsien.; Katsurai, Marie; Nguyen, Hoa N. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book constitutes the refereed proceedings of the 24th International Conference on Asia-Pacific Digital Libraries, ICADL 2022, which was held in November/December 2022. The 14 full, 18 short, and 12 poster papers presented in this volume were carefully reviewed and selected from 78 submissions. Based on significant contributions, the full and short papers have been classified into the following topics: intelligent document analysis; neural-based knowledge extraction; knowledge discovery for enhancing collaboration; smart search and annotation; cultural data collection and analysis; scholarly data processing; data archive and management; research activities and digital library; and trends in digital library. .
Intelligent document analysis -- Neural-based knowledge extraction -- Knowledge discovery for enhancing collaboration -- Smart search and annotation -- Cultural data collection and analysis -- Scholarly data processing -- Data archive and management -- Research activities and digital library -- Trends in digital library.
Keywords: Natural language processing (Computer science).; Computers; Artificial intelligence; Information storage and retrieval systems; Application software; User interfaces (Computer systems).; Human-computer interaction; Natural Language Processing (NLP).; Computing Milieux; Artificial Intelligence; Information Storage and Retrieval; Computer and Information Systems Applications; User Interfaces and Human Computer Interaction